Stressed Skin Effect on the Elastic Buckling of Pitched Roof Portal Frames. (November 2016) - Nagy, Zs.; Pop, A.; Moiș, I.; Ballok, R.
Abstract: The paper presents the influence of the diaphragm effect on the behavior of pitched roof portal frames, having Z purlins and corrugated sheeting as cladding. The paper highlights the stabilizing effect in terms of load multiplication factor—αcr on portal frames by taking into account the lateral constraints ensured by a typical cladding system—Z purlins with one layer of sheeting panels. The purpose of the paper is to make a comparison between the simplified design model of a portal frame, where the supports simulating the purlins are considered with infinite axial rigidity and a portal frame design model where the calculated stiffness of the cladding for the lateral supports is introduced manually. The obtained results highlight the importance of the diaphragm effect and refer to the variation of the load multiplication factor αcr for main structural elements. The fundamental objective of this research is to develop a relatively fast checking procedure, easy to use in the current design process, by including the diaphragm stiffness in the analysis of the pitched roof portal frames. To evaluate the benefits of stressed skin action, simplified and complex modeling techniques have been developed. Obtained results emphasize the impact of stressed skin action on structural performance of pitched roof portal frames.